Development of detection system for lead ions in mixture solutions using UV-Vis measurements with peptide immobilized microbeads - Shuhei Yoshida; Koki Yoshida; Yoshio Hamada; Takaaki Tsuruoka; Kenji Usui (Scientific Reports)
Abstract Environmental pollution caused by heavy metals are problems worldwide. In particular, pollution and poisoning by lead ions (Pb2+) continue to be common and serious problems. Hence, there is a need for a widely usable method to easily detect Pb2+ from solutions containing organic materials from environmental water such as seas, ponds, etc. Here, we established a system to easily detect Pb2+ from such mixture solutions using Pb2+ binding peptide immobilized beads (peptidyl beads) and ultraviolet (UV) absorption measurements. This method could detect Pb2+ at low concentrations equivalent to inductively coupled plasmon-atomic emission spectroscopy (ICP-AES). Using the detected values to create a calibration curve, it was found that there was a positive correlation between the concentration of Pb2+ and absorbance, which also made it possible to quantify sub-µM Pb2+ in the solutions. Furthermore, Pb2+ was detected and quantified under mixed conditions of environmental water such as seas, rivers, and ponds. This method is expected to become a versatile and easy-to-use Pb2+ detection method for end-users worldwide.